ENHANCING UNIVERSITY STUDENTS’ STUDY SUCCESS THROUGH CARING LEADERSHIP - Satu Uusiautti; Kaarina Maatta (European Scientific Journal, ESJ, 2013)
Today’s educational policies aim at making higher education more effective. However, in order to realize this in practice more attention should be paid on university students’ study processes as a whole. In this article, we discuss the factors that comprise student teachers’ study processes at universities. Especially focus will be on what are such activities in higher education administration that could enhance university students’ study success? This study is a part of a larger research project in which university leaders (n = 13) in Finland and USA were interviewed in 2012. They were asked to describe their perceptions of caring leadership at universities. In this research, the connection between caring leadership and students’ study processes was studied. According to the results, caring leadership can enhance students’ study success. We argue that universities, their leaders and educators, should be more thoughtful and willing to genuinely help and confront students as individuals. A multidimensional framework of factors affecting students’ study paths with caring leadership as the empowering element is introduced as the conclusion.